MEDIA INFOGRAFIS SEBAGAI UPAYA MENINGKATKAN KARAKTER PEDULI LINGKUNGAN BAGI GENERASI Z - Uswatun Hasanah; Vina Nur Afianah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research was to find out the benefits of applying infographics as a tool or media in conducting socialization related to efforts to improve the character of caring for the environment. One of which could be realized by doing recycling activities, mainly from types of plastic waste such as used plastic bottles used as some valuable items that have benefits and can be for sale. MI Tarbiyatul Athfal Lamongan was the subject of the research because the school was one of the schools that have implemented infographics. Qualitative descriptive was the method and approach used. Meanwhile, observation, interviews, and documentation were parts of the data analysis techniques. The observations and interviews became the primary sources in this study which were obtained directly from the school involving the principal and teachers. The results of literature studies or supporting literature were also used as a second source in research. Choosing this infographic was due to several elements, including a clear and easy-to-understand language structure and an attractive design. Thus, it would foster the readers’ interest to read it. The conclusion obtained was one of the tools or media to explain various information that would be boring if presented in long text. It was more effective and efficient if packaged in the form of infographics. In addition to the attractive appearance design, the language used was also short, clear, and easy to understand by readers so that the information to be conveyed was successfully received quickly.